Factors influencing the low numeration literacy of the low class in Duri Kepa 11 Primary School, West Jakarta - Lidya Octaveny Erpa Pardede (Institute of Computer Science (IOCS), 2023)
This research aims to analyze the factors that influence low class numeracy literacy at Duri Kepa 11 Public Elementary School, which is included in the low category and to analyze efforts to overcome the low level of lowclass numeracy literacy at Duri Kepa 11 Public Elementary School. The method used is qualitative with a descriptive approach using interviews. structured, observation and documentation. The results of the research show that the factors that influence the low numeracy literacy skills of lower grade students at SD Negeri Duri Kepa 11 can be categorized into two, namely internal factors and external factors. Internal factors include low reading ability, low concept understanding ability, and low reading interest. Meanwhile, external factors that influence include parental guidance, teacher ability, and infrastructure. Solutions that can be implemented by the school to overcome the low numeracy literacy skills of lower class students at SD Negeri Duri Kepa 11 include getting used to calistung 15 minutes before class learning activities begin, optimizing facilities and infrastructure, using models, techniques and approaches for fun learning.